FACTORS RELATED TO MINOR INJURIES IN CONSTRUCTION WORK FROM THE PERSPECTIVE OF OCCUPATIONAL HEALTH AND SAFETY - Viala, Berlian Totti; Nugroho, Bayu Yoni Setyo (HEARTY, 2025)
Construction accounts for one-third of all workplace fatalities, and construction workers have six times the risk of dying on the job compared to other sectors. Minor injuries are significant contributors to workplace accident records, with factors such as overtime and lighting playing a role. The objective of this study is to analyze the factors associated with minor injuries. The research utilized a quantitative approach with observational analytical methods, conducting a cross-sectional survey. A questionnaire was used to gather data on characteristics, overtime hours (standard of 4 hours), minor injuries, and lighting measurements (LUX Meter) with a standard of 100 lux at PT. Adhi Karya's Glapan Timur Irrigation Rehabilitation Project. The sample consisted of 53 respondents. The results of lighting measurements showed that 28 respondents (52.8%) were exposed to lighting intensity "Below Standard" and 25 respondents (47.2%) were exposed to lighting intensity "Within Standard." There was a significant relationship between lighting and the incidence of minor injuries among construction workers, with a p-value of 0.021 and an OR = 3.750. Additionally, there was a relationship between overtime and the incidence of minor injuries, with a p-value of 0.025 and an OR = 3.630. Both independent variables were associated with minor injuries.